The practicality of Problem Based Learning tools with a scientific approach to improve students’ critical thinking ability - Kusuma, Adi Candra (Unnes Journal of Mathematics Education, 2020)
The aim of this study was to obtain the practicality of Problem Based Learning (PBL) tools with a scientific approach to improve students’ critical thinking ability (KKBKM). This study was a quantitative type with research subjects of 2D class as the control class and 2F as the experimental class. Both classed consisted of 32 students in the even semester of the academic year 2018/2019. The control class was treated by using an expository learning model, while the experimental class was treated by PBL with a scientific approach. This study carried out the interview, observation, and questionnaires to collect data. Then the practicality test analysis was obtained by observation of the implementation of learning according to RPP, questionnaire for lecturers and students’ response, and observation of KKBKM activities. Afterward, the average score of learning implementation observation according to RPP was 74.2%, questionnaire of lecturers’ response was 4.17, students’ response was 86.10%, and KKBKM observation was 4.14 with an excellent predicate. Thus, the learning tool prepared positively could be used in learning.